Penyuluhan Pencegahan Hipertensi melalui Deteksi Dini Tekanan Darah di Posyandu Lansia - Zaenal, Zaenal; Jukarnain, Jukarnain; Ibrahim, Sultan Akbar (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Hypertension is a non-communicable disease that is common among the elderly and is a major risk factor for various cardiovascular complications. Early detection of blood pressure and education on hypertension prevention are crucial in the community, particularly at the elderly health post (Posyandu). This community service activity aims to increase the elderly's knowledge about hypertension prevention and early detection through routine blood pressure checks. The implementation method included counseling, interactive discussions, and direct blood pressure checks at the Posyandu. The activity results showed an increase in the elderly's understanding of the importance of maintaining a healthy lifestyle, and several elderly with high blood pressure were identified who were then referred to health facilities. This activity is expected to serve as a preventive and promotive measure to reduce the incidence of hypertension in the community.